A 2 YEAR (2019-2020) ANALYSIS OF SUICIDE REPORTS IN THE NIGERIAN MEDIA (Proceedings of the Global Public Health Conference, 2022)
Suicide is increasingly becoming a public health concern. Reporting and portrayal of suicide in media may largely contribute to this. Gaining an insight into the pattern and possible risk factors may help in the design of effective preventive measures. The aim of the study was to generate a 2-year data of suicide reportage in media in Nigeria. This was a retrospective purposive Content analysis of all media suicide reportage in Nigeria between January 2019 - December 2020.  Data was entered into an excel spread sheet. Duplication was avoided. The statistical package for social sciences, version 22 was used for analysis. Frequencies and percentages of relevant variables were generated. Chi square and Fisher’s exact test was used to assess associations. Significant value was set at p
Keywords: suicide; media; reportage; Nigeria